EFEK VARIASI BEBAN PENDINGINAN TERHADAP COEFFICIENT OF PERFORMANCE (COP) MESIN PENDINGIN PADA BOX COOLER ALAT DISTILASI - Ahmad Akromul Huda; Karyanik Karyanik; Earlyna Sinthia Dewi (Universitas Muhammadiyah Mataram, 2021)
Refrigerator has been widely used by the community and can be found in almost every shop, office building and household. The application of refrigeration machines can also be developed in many other equipment and machines, one of which is in the distillation apparatus. Distillation is a method of separating two substances. A distillation machine using a cooling machine in the condenser will be very helpful, especially for distillation. This study aims to determine the effect of cooling on the performance of the cooling machine. Cooling engine performance coefficient of achievement (COP). Load variations are carried out by adjusting the boiler temperature using a thermostat. In this study, data on the temperature and pressure of the refrigerant flowing in the refrigeration system were taken at four points, namely before entering the compressor, before entering the capillary tube and before entering the evaporator . In this study also used four variations of the cooling load given to the box cooler of 110 °C, 125 °C, 140 °C, and 155 °C. Then the temperature and pressure data is processed to get the COP value every time from all variations of the cooling load. The results showed that the increaseing in the cooling load, the smaller the COP value of the cooling machine. In its effect on the length of time the COP value of each variation of the cooling load increases. The highest COP value in this study was obtained at a cooling load temperature of 110 ºC of 10.69 and the lowest was obtained at a temperature of 155 ºC of 9.38.